A Stretchable and Safe Polymer Electrolyte with a Protecting‐Layer Strategy for Solid‐State Lithium Metal Batteries. Issue 15 (1st May 2021) - Zhang, Shengzhao; Liang, Taibo; Wang, Donghuang; Xu, Yanjun; Cui, Yongliang; Li, Jingru; Wang, Xiuli; Xia, Xinhui; Gu, Changdong; Tu, Jiangping
Abstract: An elastic and safe electrolyte is demanded for flexible batteries. Herein, a stretchable solid electrolyte comprised of crosslinked elastic polymer matrix, poly(vinylidene fluoride‐hexafluoropropylene) (PVDF‐HFP), and flameproof triethyl phosphate (TEP) is fabricated, which exhibits ultrahigh elongation of 450%, nonflammability and ionic conductivity above 1 mS cm −1 . In addition, in order to improve the interface compatibility between the electrolyte and Li anode and stabilize the solid‐electrolyte interphase (SEI), a protecting layer containing poly(ethylene oxide) (PEO) is designed to effectively prevent the anode from reacting with TEP and optimize the chemical composition in SEI, leading to a tougher and more stable SEI on the anode. The LiFePO4 /Li cells employing this double‐layer electrolyte exhibit an 85.0% capacity retention after 300 cycles at 1 C. Moreover, a flexible battery based on this solid electrolyte is fabricated, which can work in stretched, folded, and twisted conditions. This design of a stretchable double‐layer solid electrolyte provides a new concept for safe and flexible solid‐state batteries. Abstract : A stretchable polymer electrolyte is fabricated based on resilient copolymer and poly(vinylidene fluoride‐hexafluoropropylene) (PVDF‐HFP) with ultrahigh elasticity, nonflammability, and good ionic conductivity. A protective layer containing poly(ethylene oxide) (PEO) is designed to protect the electrolyte against the anode and stabilize the solid‐electrolyte interphase (SEI) during cycling. A flexible solid‐state battery is prepared using this double‐layer electrolyte, which can light a light emitting diode (LED) bulb under different deformed conditions.